Intragroup Communication Between Parents and Children in Educating Cocoa Generation in South Sulawesi - Tuti Bahfiarti; Arianto Arianto; Andi Alimuddin Unde (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2022)
The purpose of the study was to analyze the role of parents through intragroup communication in educating the next generation of children to love cocoa. A qualitative approach, namely a case study of a cocoa farmer family in educating and motivating children. Data collection techniques were non-participant observation, in-depth interviews, and The Focus Group Discussion on nine cocoa farming families with children 7-19 years old by purposive sampling. The findings of the research on the role of parents in intragroup communication first, the dominant activity of parents and their proactively taking part in children directly teaches, involves, and instils motivation. Second, the category of activity and high participation from parents. Third, the dominant child is proactive and participative, playing an independent learning role, and is motivated as a cocoa farmer. This research impacts the urgency of family communication in the regeneration's sustainability of cocoa farmers' children in supporting government programs to increase the productivity of cocoa plants.Â